The Effect of Multimedia-Based 3D Flipbook Learning Media on Physics Learning Outcomes of 11th Science Grade Students in Work and Energy Subjects - Robayat, Atmamu (Omega: Jurnal Fisika dan Pendidikan Fisika, 2018)
Research on the effect of using multimedia-based 3D flipbook learning media on physics learning outcomes of 11th science grade students in work and energy subjects has been carried out. This research is based on problems in education, especially the use of multimedia learning in the subject of work and energy in physics. Research conducted at SMA PGRI 109 Tangerang using the experimental design method in the form of posttest only with 48 students as samples that divided into 2 groups of classes, experimental class and control class.Based on the results of the analysis on the prerequisite test, using Chi Square test, the estimated results: from the experimental class and the control class, $X_\text{count} < X_\text{table}$; with a significant level of $α=0.05$, it means the research class, experimental class, and control class, are normally distributed. For the homogeneity test using the Fisher test obtained $F_\text{count} < F_\text{table}$, which is equal to $1.017 < 2.069$, then the research class is homogeneous distribution. In the last stage, hypothesis testing was performed by $t$-test and the result was $t_\text{count} = 8.621 > t_\text{table(0.05)} = 2.014$; which means $H_0$ is rejected. Based on the calculation of the hypothesis test, it can be concluded that there is the effect of the use of multimedia-based 3D flipbook learning media on physics learning outcomes for students of 11th science grade in work and energy subjects.